2007
DOI: 10.1038/nature06406
|View full text |Cite
|
Sign up to set email alerts
|

Localization of type 1 diabetes susceptibility to the MHC class I genes HLA-B and HLA-A

Abstract: The major histocompatibility complex (MHC) on chromosome 6 is associated with susceptibility to more common diseases than any other region of the human genome, including almost all disorders classified as autoimmune. In type 1 diabetes the major genetic susceptibility determinants have been mapped to the MHC class II genes HLA-DQB1 and HLA-DRB1 (refs 1-3), but these genes cannot completely explain the association between type 1 diabetes and the MHC region 4-11 . Owing to the region's extreme gene density, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

43
431
6
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(486 citation statements)
references
References 26 publications
43
431
6
6
Order By: Relevance
“…9 Furthermore, it indicates that our susceptibility locus maps away from the classical MHC, although additional risk loci are also believed to exist there, in particular for HLA-B. 25,[27][28][29] It is interesting to note that conditional logistic regression analyses in the T1DGC dataset showed that the associations with the PRSS16 SNPs and one of the BTN SNPs were independent of HLA-B, and also of the other class I loci. The associations with the PRSS16 SNPs also seemed independent of the earlier reported UBD and HLA-G associations, though some dependency was seen in the regression analyses between one of the HLA-G SNPs and one of the PRSS16 SNPs, even though there was hardly any LD between these SNPs when calculated on the basis of the entire T1DGC dataset.…”
Section: Discussionmentioning
confidence: 93%
“…9 Furthermore, it indicates that our susceptibility locus maps away from the classical MHC, although additional risk loci are also believed to exist there, in particular for HLA-B. 25,[27][28][29] It is interesting to note that conditional logistic regression analyses in the T1DGC dataset showed that the associations with the PRSS16 SNPs and one of the BTN SNPs were independent of HLA-B, and also of the other class I loci. The associations with the PRSS16 SNPs also seemed independent of the earlier reported UBD and HLA-G associations, though some dependency was seen in the regression analyses between one of the HLA-G SNPs and one of the PRSS16 SNPs, even though there was hardly any LD between these SNPs when calculated on the basis of the entire T1DGC dataset.…”
Section: Discussionmentioning
confidence: 93%
“…It has a strong genetic component. The most important genetic factors for determining the risk of developing T1DM reside in the HLA class II loci but also, according to recent findings, in the HLA-B and HLA-A class I genes [2]. Several other gene regions have also been identified: a region 5′ to the INS gene, CTLA4, PTPN22, IL2RA, and the IFIH1 region [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, numerous studies have strongly implicated additional T1D risk loci within the MHC. [3][4][5][6][7][8][9][10][11][12] This complex contains an unusually high density of genes involved in immunological responses, 13 of which many are good candidates for involvement in autoimmune processes. The observation of multiple susceptibility loci in the MHC is shared with a number of other AIDs, including ankylosing spondylitis, celiac disease, Graves' disease, juvenile idiopathic arthritis, multiple sclerosis, rheumatoid arthritis, sarcoidosis, systemic lupus erythematosus and ulcerative colitis (cf.…”
Section: Introductionmentioning
confidence: 99%